Conjunto de valores críticos generalizados e fibração - Perico Monsalve, Gabriel Esteban (2019)
This dissertation consists of a detailed study of the techniques belonging to the theory of generalized critical values announced by P. Rabier in [32], focusing on applications of three fundamental theorems. Following [25], we prove the classical Morse-Sard theorem. We present the proof of Rabier’s fibration theorem given by Z. Jelonek in [10]. Finally, we study two theorems like Morse-Sard theorem to the generalized critical values, the first one for semialgebraic differentiable mappings and the second one for complex polynomial mappings.